Caribou and Iglulik Inuit Kayaks - Arima, Eugene (ARCTIC, 1994)
A century ago the Tyrrell brothers descended the Kuu ("The River" in Inuktitut, or Thelon River). As they neared Qamani'tuaq ("The Big Broad," or Baker Lake), elegant slender kayaks appeared and easily outpaced their voyageur-driven canoes. . The Tyrrells were in the country of the Caribou Eskimos . who actually comprised several distinct named groups. The two northern ones who lived largely inland by the later 19th century are called Ha'vaqtuurmiut ("Whirlpools Aplenty People") and Qairnirmiut ("Bedrock People"). Their kayaks were especially sleek and well made, with striking long, thin horns at the ends. The stern horn angled up, while the bow horn was level after a slight jog up at its root. These eye-catching slim end horns in the Caribou and Iglulik Inuit kayak design are not only attractive but also very useful. . The characteristic end horn configuration is useful, too, as an indicator of possible historical connections. .